A quantum cognition model for simulating ethical dilemmas among multi-perspective agents. Issue 2 (2nd April 2020) - Yilmaz, Levent
ABSTRACT: Multi-agent systems are widely used in implementing systems with autonomous behaviour, as well as simulating models that involve human behaviour. Ethical decision-making is a unique aspect of such socio-cognitive systems. In situations that require deliberation over a multitude of options with ethical implications, moral dilemmas are often resolved by a range of heuristics and principles that view the situation from different perspectives. While constraint and utility-driven decision-making strategies are customary in agent-based models, the incompatibility among multiple perspectives can invalidate the underlying premises of models of probabilistic utility-based decisions that rely on classic Kolmogorov axioms. In this paper, we highlight the fallacies of such models and present a practical case study to demonstrate how quantum cognition models can provide an alternative and credible representation of decision-making behaviour in simulations that involve ethical dilemmas.